MYCOTIC INFECTION OF TINEA CAPITIS IN TEHRAN - M. Moghadami; M. Emami (Tehran University of Medical Sciences, 1986)
From 687 patients referred to the Medical Mycology Depatment of the school of public Health, 184 cases showed Tinea capitis infection, direct microscopy and culture was positive in 86.2% and 75.29% of the cases respectively. From the positive cultures 5 different dermatophtes were identified as: Microsporum canis, Trichophyton violaceum, Trichophyton verrucosum, Trichophyton schoenleinii, Trichophyton mentagrophytes. M. canis was found to be the commonest causative organism of Tinea capitis in Tehran (53, 84%) followed by T.violaceum (22.37%), T. verrucosum (13.98%), T.shoenleinii (11.18%) and T.mentagrophytes (6.69%). Candida albicans and other candida species were also isolated from two patients.